Early-life origins of disparities in chronic diseases among Indigenous youth: pathways to recovering health disparities from intergenerational trauma. (18th September 2018) - Phillips-Beck, W.; Sinclair, S.; Campbell, R.; Star, L.; Cidro, J.; Wicklow, B.; Guillemette, L.; Morris, M. I.; McGavock, J. M.
Abstract: Indigenous women and children experience some of the most profound health disparities globally. These disparities are grounded in historical and contemporary trauma secondary to colonial atrocities perpetuated by settler society. The health disparities that exist for chronic diseases may have their origins in early-life exposures that Indigenous women and children face. Mechanistically, there is evidence that these adverse exposures epigenetically modify genes associated with cardiometabolic disease risk. Interventions designed to support a resilient pregnancy and first 1000 days of life should abrogate disparities in early-life socioeconomic status. Breastfeeding, prenatal care and early child education are key targets for governments and health care providers to start addressing current health disparities in cardiometabolic diseases among Indigenous youth. Programmes grounded in cultural safety and co-developed with communities have successfully reduced health disparities. More works of this kind are needed to reduce inequities in cardiometabolic diseases among Indigenous women and children worldwide.